Investigating changes to food web structure after fish removal using size spectra analysis - Tyler J. Butts; Martin A. Simonson; Michael J. Weber; Grace M. Wilkinson (Ecosphere)
Abstract Biomanipulation can control eutrophication, but if there is no discernible change, it is difficult to disentangle whether the biomanipulation failed to substantially alter food web structure or was unable to overcome external nutrient loading. Traditional food web model analyses to monitor management interventions can be prohibitively time and data‐intensive. Size spectra, the relationship between species abundance and body size, could be used to detect changes in food web structure following major disturbances. We fit size spectra in six shallow lakes in northwest Iowa from 2018 to 2020, four of which underwent commercial harvest of common carp (Cyprinus carpio) and bigmouth buffalo (Ictiobus cyprinellus) during this period, with two lakes serving as unmanipulated references. There were no improvements in water quality metrics in any of the lakes. Based on the size spectra slopes, there were also no significant changes in species size structure due to harvest or harvest intensity of common carp or bigmouth buffalo. Size spectra height (an index of overall organism size) decreased across all years in all lakes, likely reflecting broadscale regional influences. We demonstrated that incentivized harvest was unable to significantly shift size spectra slopes as intended, providing evidence that the lack of improvements in water quality may be due to a failure to induce strong top‐down effects, despite substantial removals of bigmouth buffalo and common carp. We also provide support to the assumption that size spectra height is related to ecosystem productivity and show size spectra dynamics in extremely eutrophic ecosystems. Furthermore, we illustrate that size spectra analyses can be a powerful tool to understand and assess food web‐focused management interventions.